1993
DOI: 10.1111/j.1550-7408.1993.tb04479.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pneumocystis carinii Preparations Developed for Lipid Analysis

Abstract: Pneumocystis carinii organisms were isolated from viral antibody-negative rats that had been infected by intratracheal intubation of organism preparations tested negative for common bacteria and fungi. Infection scores of lungs from infected animals at the time of parasite isolation was > 5 (100-1,000 organisms/oil immersion field). Electron microscopy of heavily infected lungs revealed that the pathogens adhered to Type I pneumocytes and to each other, resulting in obstructions up to several cell layers thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 22 publications
7
82
0
Order By: Relevance
“…Results from the present study are in general agreement with those from previous studies from other laboratories (19,21,26). Our analyses showed that the major lipids in P. carinii include phosphatidylcholine, phosphatidylethanolamine (26), and cholesterol (19).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Results from the present study are in general agreement with those from previous studies from other laboratories (19,21,26). Our analyses showed that the major lipids in P. carinii include phosphatidylcholine, phosphatidylethanolamine (26), and cholesterol (19).…”
Section: Resultssupporting
confidence: 83%
“…We found no evidence for the presence of either phosphonolipids or DGTS (data not shown). Cholesterol was the major sterol present in all of our preparations examined as described previously (21), and the percentage of cholesterol observed (approximately 80%) agrees in general terms with that reported previously (21). Thus, while this is the first report that identifies sterols other than cholesterol in P. carinii preparations, other studies have reported that cholesterol does not constitute the entire sterol content of the organism.…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, no evidence of direct ergosterol precursors were detected; trienes, tetraenes and ⌬ 5,7 sterol nuclei were not detected. The inability to detect ergosterol by all highly sensitive analytical methods and instrumentation used in this study further verifies that P. carinii prepared from our rat model and purified by our protocol (18) are pure and free from other fungi that synthesize this sterol. If ergosterol were present in this large pooled P. carinii total sterol sample, it should have been detected in this study or in previous studies using GLC-MS techniques.…”
Section: Resultsmentioning
confidence: 99%
“…carinii organisms were isolated from the lungs of athymic mice using a modification of the method of Kaneshiro et al (36). Athymic mice infected with P. carinii were killed during pentobarbital anesthesia, and the lungs were perfused via the right ventricle with NaCaHEPES buffer (150 mM NaCl, 1.8 mM CaCl 2 , and 25 mM HEPES, pH 7.4) containing 0.5% glutathione and then were removed aseptically.…”
Section: Isolation Of P Carinii Organisms For In Vitro Studymentioning
confidence: 99%